2020
DOI: 10.1186/s12879-020-4830-5
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study on the risk factors for hemorrhagic fever with renal syndrome

Abstract: Background: Hemorrhagic fever with renal syndrome (HFRS) is an endemic communicable disease in China, accounting for 90% of total reported cases worldwide. In this study, the authors want to investigate the risk factors for HFRS in recent years to provide the prevention and control advices. Methods: A community-based, 1:2 matched case-control study was carried out to investigate the risk factors for HFRS. Cases were defined as laboratory-confirmed cases that tested positive for hantavirus-specific IgM antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
(25 reference statements)
1
7
0
1
Order By: Relevance
“…Our research showed that of the patients assessed, middle-aged patients were predominantly affected. Furthermore, most patients were men, and the main occupation was farming, consistent with the findings of previous reports 1 , 13 , 14 , 25 . The risk prediction model showed that cultivated land was the highest risk factor for HFRS 16 .…”
Section: Discussionsupporting
confidence: 91%
“…Our research showed that of the patients assessed, middle-aged patients were predominantly affected. Furthermore, most patients were men, and the main occupation was farming, consistent with the findings of previous reports 1 , 13 , 14 , 25 . The risk prediction model showed that cultivated land was the highest risk factor for HFRS 16 .…”
Section: Discussionsupporting
confidence: 91%
“…As hantaviruses may remain infective up to 15 days in a temperate environment, and up to 24 h for environmental temperature up to 37 • C [79,80], a direct and known interaction with the competent hosts is not required and may occur unnoticed. Therefore, living in a rural environment and/or in precarious, non-hygienic settings, and any interaction with environments potentially shared by the competent hosts represent the most significant risk factors for hantavirus infection [6,50,81,82]. In other words, any variation and/or combination of the aforementioned factors directly influences the actual risk profile of the targeted population.…”
Section: Discussionmentioning
confidence: 99%
“…Hantaviruses also pose a risk to food consumption as well if improperly stored (Risteska-Nejashmikj et al, 2019;Wang et al, 2020). Hantaviruses, with PUUV and ANDV being studied, are not easily digested by stomach acids and can survive long enough to be passed into the gastrointestinal tract.…”
Section: Unconventional Warfare Settings and Civilian Targetsmentioning
confidence: 99%